До невизначеності в параметричних схемах ситуацій задач прийняття рішень - Ivanenko, V. I.; Mykhalevich, V. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
A sufficiently broad class of parametric problems of decisionmaking, considered from the point of obtaining the criteria of optimality, the relationship of preferences on the solution, can be divided into two subclasses: problem with uncertainty (equivocation of the solution) and problems without uncertainty (so-called deterministic problems). Criterion of existence of uncertainty is necessary for classification, and such criterion are suggested in the work.